Hybrid Artificial Bee Colony and Ant Colony Optimization Based Power Aware Scheduling for Cloud Computing - Kaur, Navdeep; Kumar, Anil (International Journal of Computer Sciences and Engineering, 2025)
Cloud Comptuing is the act of utilizing a system of remote servers facilitated on the Internet to store, oversee, and prepare information, as opposed to a nearby server or an individual computer . The organization piece based procedures that are mindful from the server determination from the cloud can progress to the cost and adequacy of distributed computing. In this we concentrated on the distinctive swarm savvy based vitality proficient procedures called Ant settlement enhancement and Particle swarm streamlining based methods. There are different planning systems like the utilization of Ant settlement improvement has demonstrated a low convergence rate to the genuine worldwide least even at high quantities of measurements Artificial bee colony optimization algorithm has been widely accepted as a global optimization algorithm of current interest for distributed optimization and control. Particle swarm advancement is restricted to introductory arrangement of particles, wrongly chose particles tends to poor results. In order to overcome these constrains a new hybrid Artificial bee colony and ant colony optimization algorithm for cloud computing environment will be proposed to enhance the energy consumption rate further.